2013
DOI: 10.1002/chem.201301444
|View full text |Cite
|
Sign up to set email alerts
|

Part I: The Development of the Catalytic Wittig Reaction

Abstract: We have developed the first catalytic (in phosphane) Wittig reaction (CWR). The utilization of an organosilane was pivotal for success as it allowed for the chemoselective reduction of a phosphane oxide. Protocol optimization evaluated the phosphane oxide precatalyst structure, loading, organosilane, temperature, solvent, and base. These studies demonstrated that to maintain viable catalytic performance it was necessary to employ cyclic phosphane oxide precatalysts of type 1. Initial substrate studies utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 69 publications
1
47
0
Order By: Relevance
“…Based on the experimental details presented in Table 1 (6). Based on the experimental details presented in Table 3 (entry 1), yield: 91%; colorless oil; 31 Dimethyl-phenylphosphine (8). Based on the experimental details presented in Table 4 General Procedure for the Deoxygenation of 1-Phenyl-3-methyl-3-phospholene 1-Oxide (9), and for the Trapping of the Phosphine (10) so Obtained A mixture of 0.11 g (0.55 mmol) of 1-phenyl-3methyl-3-phospholene 1-oxide (9) and 0.068 mL (0.55 mmol) of PS or 0.19 mL (1.1 mmol) of TMDS or 0.042 mL (1.1 mmol) of PMHS was heated under nitrogen atmosphere at the appropriate temperature in a glass bomb immersed in an oil bath or in a commercial MW vial in the MW oven for the appropriate time.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the experimental details presented in Table 1 (6). Based on the experimental details presented in Table 3 (entry 1), yield: 91%; colorless oil; 31 Dimethyl-phenylphosphine (8). Based on the experimental details presented in Table 4 General Procedure for the Deoxygenation of 1-Phenyl-3-methyl-3-phospholene 1-Oxide (9), and for the Trapping of the Phosphine (10) so Obtained A mixture of 0.11 g (0.55 mmol) of 1-phenyl-3methyl-3-phospholene 1-oxide (9) and 0.068 mL (0.55 mmol) of PS or 0.19 mL (1.1 mmol) of TMDS or 0.042 mL (1.1 mmol) of PMHS was heated under nitrogen atmosphere at the appropriate temperature in a glass bomb immersed in an oil bath or in a commercial MW vial in the MW oven for the appropriate time.…”
Section: )mentioning
confidence: 99%
“…It has been a challenge to develop catalytic versions of these reactions involving the recycling of the waste cyclic phosphine oxides in in situ reduction [6]. O wide range of phosphine oxides including mainly phospholene-and phospholane derivatives [7][8][9][10]. In these cases, the phosphoranes were formed in situ by the quaternization of the phosphine by the α-haloacetic ester [7][8][9] or even an unactivated alkyl halide [8], followed by dehydrohalogenation by Na 2 CO 3 [7,9], diisopropylethylamine [8], or in situ generated t BuONa [10].…”
Section: Introductionmentioning
confidence: 99%
“…These problems can be eliminated by applying the phosphine in a catalytic amount, and by insuring the in situ reduction of the phosphine oxide formed. This was first elaborated for the Wittig reaction using silanes as the reducing agent by O'Brien . Since then, the catalytic Wittig reaction has become a hot topic and found a number of applications .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently they reported that the soluble organic base N , N -diisopropylethylamine was a good replacement for sodium carbonate in such reactions [19], and that the addition of 4-nitrobenzoic acid facilitated the phosphine oxide reduction step using phenylsilane (PhSiH 3 ) instead of diphenylsilane [20]. Using this combination of 4-nitrobenzoic acid and phenylsilane for phosphine oxide reduction allowed reactions starting with phosphine oxide 24 (Fig.…”
Section: Reviewmentioning
confidence: 99%